Tafsir Sufi Ishariy in the Methods of Sufi Practice: A Critical Study on Ibn ‘Ajibah’s Tafsir al-Bahr al-Madid - Hashim, M. (Universiti Sains Islam Malaysia, 2024)
Tafsir Sufi Ishariy is one of the types of the Quranic exegesis based on interpretations of verses that differ from the classical commentaries. This research aimes to define Tafsir Sufi Ishariy, Ibn ‘Ajibah and his life. The paper as well extrapolates Tafsir Sufi Ishariy for Quranic verses in the book which related to the issue of the methods of practice. The methodology for this research in analyzing information depends on the descriptive and critical approach. The findings indicate that the Tafsir Sufi Ishariy by Ibn ‘Ajibah partly match and partly contradict the conditions of Tafsir Sufi Ishariy in this issue. In fact, if Ibn ‘Ajibah limited his interpretation to his Ishari Batiniy views without authorization of the commentaries outwardly, there would have been no differences between him and the doctrine of Shiites Batiniyyah. However his scholarly Tafsir, his confirmation of commentaries outwardly and his condemnation of Batiniyyah understanding make his Tafsir Ishariy valid and well concerned.